Numerical studies on the smoke control by water mist screens with transverse ventilation in tunnel fires. (April 2017) - Liang, Qiang; Li, Yangfeng; Li, Junmei; Xu, Hui; Li, Kaiyuan
Graphical abstract: Research paper: A new smoke control strategy system that combined water mist screens with transverse ventilation system (WMSTV system) was developed for potential fires in long road tunnels. In this strategy, water mist screens were used to confine the fire and smoke, and smoke can be eliminated by transverse ventilation system timely in the fire zone. The results of numerical simulation by FDS show that the WMSTV system is a good strategy for smoke control in tunnel fires. Highlights: A new smoke control strategy that combined water mist screens with a transverse ventilation system was developed for potential fires in long road tunnels. Numerical simulation was carried out to analyze the effectiveness of WMSTV system in tunnel using FDS 5.0. Through comparative analysis of three smoke control strategies, the results show that the WMSTV system is the best strategy for smoke control in tunnel. Abstract: Emergency ventilation systems are commonly used for smoke control during tunnel fires. For the transverse ventilation system, high efficiency for fire safety could be obtained by confining the smoke within certain zones. In this paper, a new system with simultaneous water mist screen and transverse ventilation system (WMSTV system) is proposed. In the WMSTV system, water mist screens are used to confine smoke from spreading widely, which assists the smoke exhausting process of the transverse ventilation system. Numerical method is used for investigation in this paper. The effects of natural and transverse ventilation systems without water mist are also investigated for comparison. Numerical results show that the WMSTV system can confine the fire and smoke effectively and the environment inside the confined zone would be suitable for occupants evacuation and firefighting. The system can be regarded as a feasible strategy for smoke control in tunnels.